Cover Feature: Nanosecond Pulsed Laser‐Heated Nanocrystals Inside a Metal‐Organic Framework Matrix (ChemNanoMat 6/2022). Issue 6 (17th May 2022) - Niemeyer, Max; Bessel, Patrick; Rusch, Pascal; Himstedt, Rasmus; Kranz, Daniel; Borg, Hadir; Bigall, Nadja C.; Dorfs, Dirk
Abstract : A ZIF‐8 metal organic framework matrix is used to investigate the effects of nanosecond laser‐pulse‐driven plasmonic heating of gold nanoparticles. Cavities in the matrix material around the particles after laser irradiation indicate a temperature rise up to 750 K and above in a confined distance of 2‐45 nanometers. Experiments with gold‐zinc oxide heteroparticles give insight in the heat conduction between the particle components. More information can be found in the Research Article by Dirk Dorfs et al.